Efektivitas Event Sponsorship dalam Meningkatkan Brand Awareness dan Penjualan Produk Telkomsel Branch Surabaya - Dwiridotjahjono, Jojok; Sitanggang, Della Anzelia; Tandiayuk, Jurycha (Ikatan Da'i Indonesia, 2025)
This paper aims to analyze the effectiveness of event sponsorship implemented by PT Telkomsel Branch Surabaya to increase brand awareness and product sales. The method used is participatory with a qualitative approach, where all related parties are directly involved in the effectiveness of event sponsorship activities to increase brand awareness and product sales at PT Telkomsel Branch Surabaya. The results show that event sponsorship carried out by PT Telkomsel Branch Surabaya has proven effective in increasing brand awareness and product sales, because through this event sponsorship activity, PT Telkomsel Branch Surabaya can promote products directly to the right audience. This event sponsorship can also attract attention and create a positive experience to increase brand awareness and purchase of Telkomsel products.